Toxicity of Nitrite to Juvenile Sunray Surf Clam (Mactra chinensis Philippi) - Yuanyuan Dai; Yubo Dong; Huimin Wu; Zilong Chen; Feng Yang; Jia Jia; Zhongzhi Chen (Pollutants)
Nitrite is a common pollutant in marine environments and can cause mortality in crustaceans and bivalves. The purpose of the current study is to understand nitrate’s toxicity to juvenile clams due to its potential impact on aquaculture and marine ecosystems. Juvenile sunray surf clams (Mactra chinensis Philippi) (1.00 ± 0.10 cm shell length, 0.75 ± 0.04 cm shell height) were exposed to varying concentrations of nitrite for 96 h and 20 days, respectively. The LC50 for survival at 96 h was 37 mg/L NO2-N. Histological evaluations were made on juvenile clams exposed at 30 mg/L after 20 d of exposure. Epithelial cells and digestive diverticulum are the best sub-lethal effect indicators. Shell length and antioxidant enzyme activities were measured at the beginning of the experiment and then observed 10 and 20 days after exposure. A logarithmic relationship was obtained between the relative growth rate (based on the shell length) of juvenile M. chinensis and the nitrite concentration. Compared to the control, activity suppression of superoxide dismutase and catalase activity was detected from the concentration of 1 mg/L NO2-N. It is recommended that nitrite concentrations remain below 1 mg/L to prevent stress during the early developmental stages of clams.